2021
DOI: 10.24292/01.or.420010221
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic management of arrhythmia – radiosurgery in treatment of ventricular tachycardia (SMART-VT) – clinical trial protocol and study rationale

Abstract: Patients with vetricular tachycardia are usually treated with antiarrhythmic drugs and ablation if the arrhythmia substrate is available for invasive treatment. Despite high efficiency of this treatment there is a significant group of patients who do not benefit from available treatment methods, either because they cannot be applied or do not allow for durable control of the disease. For that reason a novel treatment method, STereotactic Arrhythmia Radioablation (STAR) has been proposed and its safety and effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…STereotactic Arrhythmia Radioablation is challenged by significant conceptual variability between centers. The target delineation can be based on non-invasive cardiac mapping ( 4 ), invasive EAM ( 8 ), or even primarily on 12-lead ECG and medical imaging ( 18 ). The transfer process of the EAM data to radiotherapy planning systems ranges from indirect comparison to software-based transformations ( 9 ), and the median volume of the final structures varies almost sevenfold between centers ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STereotactic Arrhythmia Radioablation is challenged by significant conceptual variability between centers. The target delineation can be based on non-invasive cardiac mapping ( 4 ), invasive EAM ( 8 ), or even primarily on 12-lead ECG and medical imaging ( 18 ). The transfer process of the EAM data to radiotherapy planning systems ranges from indirect comparison to software-based transformations ( 9 ), and the median volume of the final structures varies almost sevenfold between centers ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The trial is ongoing and registered under the ClinicalTrials.gov identifier of NCT04642963. A thorough description of the trial protocol can be found in a previously published article ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…The target volume contouring was performed on the spot, using a remote access workstation, through indirect comparison of EAM data and contrast-enhanced CT fused with Deep Inspiration Breath Hold (DIBH) treatment planning CT. The organs-at-risk (OARs) and derivative structures were prepared according to the study protocol ( 10 ). Using Volumetric Modulated Arc Therapy (VMAT) technique, three 6 MeV flattening filter-free photon beam fields, DIBH respiratory motion management, a dose of 25 Gy was delivered to the planning target volume (PTV) ( Figure 3A ).…”
Section: Case Reportmentioning
confidence: 99%
“…Dose constraints for OARs and dose to target are presented in table below ( Table 1 ). Most of them are based on values for thoracic stereotactic radiotherapy, however, dose constraints for coronary arteries have been extrapolated form available data with principle of maximum safety ( 10 ). Each RT fraction is supervised by a cardiologist.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation